Pelota: A double-edged sword in virus infection - Li, Xue; Zhou, Xueping; Li, Fangfang (PLoS pathogens, 2025)
Pelota, a conserved ribosome rescue factor involved in mRNA surveillance, has emerged as a pivotal player in host–virus arms race. Beyond its canonical role in maintaining translational fidelity via No-Go Decay and Non-Stop Decay pathways, Pelota exhibits a dual function during viral infection-serving either as a restriction factor or as a susceptibility element depending on the virus species and their hosts. In DNA virus infections, notably with geminiviruses, a natural mutation in Pelota confers recessive resistance in tomato and pepper probably by impairing viral protein translation, offering valuable insights for resistance breeding. Conversely, in RNA virus infections, Pelota usually restricts viral propagation through RNA quality control, yet can also promote viral replication by facilitating ribosome recycling and translation. This paradox reflects a fine-tuned balance in host–virus adaption and co-evolution. Additionally, pelota mutations can modulate immune signaling pathways, with some alleles triggering enhanced resistance or autoimmunity phenotypes in plants. Meanwhile, viruses have evolved counterdefense strategies, including targeted degradation or SUMOylation interference, to subvert the Pelota’s function. Together, these findings position Pelota as a double-edged sword in viral infection, highlighting its potential as a novel target for antiviral strategies through precise genetic manipulation.